2015
DOI: 10.2298/ciceq140618044p
|View full text |Cite
|
Sign up to set email alerts
|

Pressure drop in packed beds of spherical particles at ambient and elevated air temperatures

Abstract: The aim of this work was the experimental investigation of the particle friction factor for air flow through packed bed of particles at ambient and elevated temperatures. The experiments were performed by measuring the pressure drop across the packed bed, heated to the desired temperature by hot air. Glass spherical particles of seven different diameters were used. The temperature range of the air flowing through the packed bed was from 20?C to 350?C and the bed voidages were from 0.3574 to 0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 0 publications
0
11
0
Order By: Relevance
“…For smooth spheres, it tends to over-predict f b in the high Re b range (Re b > 700) [14][15][16]; (b) if the bed particles are non-uniform in sizes, the Sauter mean diameter of particles should be used in the application of the Ergun equation; (c) when particle shape deviates significantly from a sphere, the Ergun equation tends to under-predict f b [17]; and (d) wall effects can be important when D b /d p < 10. When wall effects are important, the experimental data show deviation from the predictions of the Ergun equation [18]. can be important when < 10 ⁄…”
Section: Of 23mentioning
confidence: 99%
See 1 more Smart Citation
“…For smooth spheres, it tends to over-predict f b in the high Re b range (Re b > 700) [14][15][16]; (b) if the bed particles are non-uniform in sizes, the Sauter mean diameter of particles should be used in the application of the Ergun equation; (c) when particle shape deviates significantly from a sphere, the Ergun equation tends to under-predict f b [17]; and (d) wall effects can be important when D b /d p < 10. When wall effects are important, the experimental data show deviation from the predictions of the Ergun equation [18]. can be important when < 10 ⁄…”
Section: Of 23mentioning
confidence: 99%
“…. When wall effects are important, the experimental data show deviation from the predictions of the Ergun equation [18]. Figure 5 shows the prediction of the packed bed friction factor as a function of packed bed Reynolds number using the Ergun equation, Equation (37).…”
Section: Of 23mentioning
confidence: 99%
“…A large number of correlations of the pressure drop in packed beds of spherical and non-spherical particles have been proposed. Among plenty of overviews of those correlations are those given by (Erdim, Ömer Akgiray, & Demir 2015;Kaludjerovic-Radoicic, Boskovic-Vragolovic, Garic-Grulovic, Djuris, & Grbavcic 2017;Pavlišič, Ceglar, Pohar, & Likozar 2018;Pesic, Kaludjerovic-Radoicic, Boskovic-Vragolovic, Arsenijevic, & Grbavcic 2015;Wang et al 2017). The most widely used equation for pressure drop in packed beds, the Ergun equation is valid for the incompressible flows through packed beds with neglected wall-to-bed effects and for Re' p numbers in the range 1.2<Re' p <4200.…”
Section: Introductionmentioning
confidence: 99%
“…However, research of pressure drop in packed beds at elevated temperatures is sparse (Luckos & Bunt 2011;Pesic et al 2015;Quintana-Solórzano, Che-Galicia, Trejo-Reyes, Armendáriz-Herrera, & Valente 2018). Luckos and Bunt (2011) found that the values of the pressure drop in a commercial gasifier, calculated according to the Ergun's equation (Ergun 1952), are not satisfactory because of the variation of temperature, composition and pressure of the gases flowing through the packed bed of coal particles in the investigated gasification process.…”
Section: Introductionmentioning
confidence: 99%
“…There exists a variety of correlations for the prediction of the pressure drop in a fixed bed. A collection can be found by Pešić et al [1], according to which the pressure drop is influenced by the characteristic diameter, the diameter ratio of the packing elements, the filling height, the superficial velocity, the type of the fluid used, and the porosity (e) of the bed. In this context, the porosity is the void fraction of the packed bed.…”
Section: Introductionmentioning
confidence: 99%